Recovery of byproducts from acid mine drainage treatment - Fosso-Kankeu, Elvis, 1974-; Wolkersdorfer, C. 1964-; Burgess, Jo (Wiley-Scrivener, 2020)
"Recent developments have provided the opportunity to recover valuable materials from AMD treatment; this is a sustainable approach that allows to reduce waste while generating incomes that balance the cost of the treatment. This book provides insights to innovative and affordable routes for AMD valorisation that can certainly motivate the mining industry to effectively manage their wastes and minimize environmental impact while generating jobs opportunities"--